Study of the areas and thicknesses of mesiobucal root canals prepared by three endodontic techniques Estudo das áreas e espessuras de canais radiculares mésio-vestibulares preparados por três técnicas endodônticas - Isa Geralda Teixeira Constante; Harry Davidowicz; Fernando Branco Barletta; Abilio Albuquerque Maranhão de Moura (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The purpose of this study was to compare, in vitro, by means of computerized analysis of digital radiographic images, the anatomic alterations produced in the mandibular molar tooth dentinal walls of mesiobucal canals with severe curvature by three different endodontic techniques: Progressive Preparation, Staged and Serial Preparation. A selection was made of 45 extracted, human, mandibular molars, with root curvatures greater than 25°. They were divided into three groups for every technique studied, which were then sub-divided into three sub-groups in accordance with the position of the curvature along the root: cervical, median or apical. After access surgery and tooth length determination, the canals were filled with 100% Barium Sulphate radiological contrast and the teeth were then radiographed with a direct digital radiography system, using a special apparatus capable of keeping the samples in the same spatial position during the different radiographic takes. After the above-mentioned endodontic techniques had been performed, the teeth were again filled with Barium sulphate and were also radiographed under the same previously mentioned conditions. The pre- and post-operative digital images were then analyzed in two computerized programs, AutoCAD 2004 and CorelDraw 10, to assess, respectively, the areas and the horizontal alterations which occurred in the internal and external walls of the root canals. The results indicated that although no significant differences among the techniques were shown in the statistical analysis, in a descriptive analysis the Progressive Preparation technique was shown to be more regular, uniform and effective. Objetivou-se comparar, in vitro, através de análise computadorizada de imagens radiográficas digitais, as alterações anatômicas promovidas nas paredes dentinárias de canais mésio-vestibulares com curvatura severa de molares inferiores por três técnicas endodônticas diferentes: Preparo Progressivo, Escalonada e Seriada. Foram selecionados 45 molares inferiores humanos extraídos, com curvaturas radiculares superiores a 25°, que foram divididos em três grupos para cada técnica estudada e subdivididos em três subgrupos de acordo com a posição da curvatura ao longo da raiz: cervical, mediana ou apical. Após cirurgia de acesso e odontometria, os canais foram preenchidos com contraste radiológico de sulfato de Bário a 100% e os dentes então foram radiografados por um sistema de radiografia digital direta, utilizando-se um aparato capaz de manter as amostras na mesma posição espacial nas diferentes tomadas radiográficas. Após a realização das técnicas endodônticas supracitadas, os dentes foram novamente preenchidos com o sulfato de Bário e radiografados nas mesmas condições anteriores. As imagens digitais pré e pós-operatórias foram então analisadas em dois programas computadorizados, o AutoCAD 2004 e o CorelDraw 10, para verificar, respectivamente, as áreas e as alterações horizontais ocorridas nas paredes internas e externas dos canais radiculares. Apesar de não ter havido diferenças significantes entre as técnicas na análise estatística, em uma análise descritiva a técnica do Preparo Progressivo mostrou-se mais regular, uniforme e eficaz.